Immediate effect of electrical vestibular stimulation on autonomic and respiratory parameters and reaction time in patients with Parkinson’s disease - Asha G; Varun Manjunath; Karthik N; Yashica Gowda R; Sai Sailesh Kumar Goothy; Rohit Singh Chouhan; Anitha Lakshmi (Asian Journal of Medical Sciences)
Background: Both the electrical and natural vestibular stimulation were reported to alter both the blood pressure and motor output of respiration. After a thorough review of the literature, the studies observed the immediate effect of vestibular stimulation on autonomic and respiratory functions is sparse. Hence, the present study was undertaken.